2020
DOI: 10.1155/2020/6894684
|View full text |Cite
|
Sign up to set email alerts
|

miR-210 in Exosomes Derived from Macrophages under High Glucose Promotes Mouse Diabetic Obesity Pathogenesis by Suppressing NDUFA4 Expression

Abstract: Objective. Type 2 diabetes mellitus (T2DM) is featured by insulin resistance and lipid metabolism dysregulation. A large number of miRNAs were identified in exosomes derived from adipose tissue macrophages associated with T2DM pathogenesis, but its pathogenic roles remain unknown. This study is aimed at investigating the function of miR-210 in diabetic obesity. Methods. Exosomes from mouse macrophage RAW264.7 cells were characterized by electron microscopy, combined with biomarker expression by western blot. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…MiR-210 was detectable in the extracellular milieu of LPS-stimulated murine or human macrophages and in the plasma of both septic mice and patients. Released miR-210, free or in exosomes, might regulate (metabolic) gene expression of neighboring cells as shown, for miR-210 (40) and other miRs (8,63,64) in different contexts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…MiR-210 was detectable in the extracellular milieu of LPS-stimulated murine or human macrophages and in the plasma of both septic mice and patients. Released miR-210, free or in exosomes, might regulate (metabolic) gene expression of neighboring cells as shown, for miR-210 (40) and other miRs (8,63,64) in different contexts.…”
Section: Discussionmentioning
confidence: 93%
“…on June 6, 2021 http://advances.sciencemag.org/ Downloaded from Soluble markers of sepsis are so far missing. It has been recently demonstrated that miR-210 can be found in the exosomes of a transformed cell line of macrophage origin (40). Therefore, we checked whether the levels of miR-210 in the medium mirrored its expression in macrophages.…”
Section: Regulation Of Mir-210 In Human Monocytes and Macrophages Might Represent A Diagnostic And Prognostic Biomarker For Sepsismentioning
confidence: 99%
“…Recently, Tian et al ( 69 ) demonstrated that exosomal miR-210 from high-glucose–induced macrophages inhibited NADH dehydrogenase (ubiquinone) 1ɑ subcomplex 4 (NDUFA4) expression and induced the suppression of glucose uptake in adipocytes. NDUFA4 is one of the subunits of mitochondrial respiratory chain complex IV, and thus it is involved in mitochondrial function ( 70 ).…”
Section: Function Of Adipocyte-derived Extracellular Mirnas In Insulin Resistancementioning
confidence: 99%
“…In patients suffering from obesity, mir-210 is overexpressed in ATM [283]. Moreover, miR-210 resulted from ATM is implicated in the pathogenesis of diabetes in obese mouse models by altering glucose uptake and mitochondrial complex IV activity by targeting NADH dehydrogenase ubiquinone 1 alpha subcomplex 4 gene [308].…”
Section: Mir-210mentioning
confidence: 99%